The motion and control of a complex three-body space tethered system. Issue 10 (15th November 2017) - Shi, Gefei; Zhu, Zhanxia; Chen, Shiyu; Yuan, Jianping; Tang, Biwei
Abstract: This paper is mainly devoted to investigating the dynamics and stability control of a three body-tethered satellite system which contains a main satellite and two subsatellites connected by two straight, massless and inextensible tethers. Firstly, a detailed mathematical model is established in the central gravitational field. Then, the dynamic characteristics of the established system are investigated and analyzed. Based on the dynamic analysis, a novel sliding mode prediction model (SMPM) control strategy is proposed to suppress the motion of the built tethered system. The numerical results show that the proposed underactuated control law is highly effective in suppressing the attitude/libration motion of the underactuated three-body tethered system. Furthermore, cases of different target angles are also examined and analyzed. The simulation results reveal that even if the final equilibrium states differ from different selections of the target angles, the whole system can still be maintained in acceptable areas.